Efforts to Improve Student Learning Outcomes Through the PBL Model for Class IV Students at SDN Pejagan 3 - Siti Aisyah, Siti Aisyah; Makkiyah, Nurul; Rohandy, Urvia (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
This research aims to increase understanding of mathematical concepts, especially regarding flat shapes, namely by taking measurements of an object and understanding the characteristics of shapes in flat shapes by applying the Problem Based Learning (PBL) model so that students will think logically, critically, and actively. and enthusiastic about learning mathematics because there are activities that are interesting and relevant to everyday life which can increase their understanding and interest in this subject.The implementation of this research used several steps, including: initial planning, implementation and observation, reflection, and revised plans. This research was carried out at the Pejagan 3 Bangkalan State Elementary School for class IV students, using the Problem Based Learning (PBL) model approach which is expected to help students solve problems that exist in the process of learning activities by holding direct practice in the field with examples of real objects. . For example, by giving examples of flat shapes in the classroom such as; books, tables, paper, etc. so that students don't just know the theory.The Problem Based Learning (PBL) approach applied in this research was proven to be effective in improving the abilities and learning outcomes of class IV students at SDN Pejagan 3 Bangkalan because there was a significant increase in the average student scores from cycle I by (65) and cycle II by (98) as well as an increase in the level of learning completeness from cycle I (65,21%) to cycle II (97,82%). Therefore, it can be concluded that using this approach is very effective in improving mathematics learning. Abstract must be written briefly and factually in English.